APPLICATION OF GSQUAL-KANO AND QUALITY FUNCTION DEPLOYMENT (QFD) IN IMPROVING GREEN HOTEL SERVICES - Rizky Ardian Saputra; Kifayah Amar; Saiful Mangngenre (Journal of Industrial Engineering Management, 2023)
This study aims to examine the green practices that have been implemented in an eco-hotel and further design services to meet the customer expectation. The data was collected through a survey distributed via e-form to 250 hotel guests who personally experienced green services at the hotel. Through the integration of Green SERVQUAL (GSQual) and the KANO model, there are 11 attributes that need to be improved. Further, the improvement of green services is prioritized using the technical importance score from the QFD. The highest rating of technical importance is 376.62, indicating the need to install an automatic faucet sensor to reduce water consumption waste. By implementing the improvements, the hotel will be able to better manage its water consumption and thus satisfy their customers.